Data Integration Through WebGIS to Inform Spatial Status of Coral Reefs in Lampung Province, Indonesia - Adib Mustofa; Budhi Agung Prasetyo (Politeknik Negeri Batam, 2020)
Data integration of structured ecosystem monitoring is crucial to support decision making for better marine ecosystem management. Coral reef monitoring data had been carried out in several separated studies in Lampung Province. However, lacks data integration among scientists and institutions making them inefficient as a basis of science for ecosystem management and decision making. This study was aimed to integrate available coral reef data in the last 15 years in Lampung Province and inform the spatial status of coral reef cover through WebGIS. Secondary data of coral reef study in the last 15 years were acquired from published articles and online-available-institutional reports. Data were then converted to digital mode prior to publishing them in the form of a website database through WebGIS. Results suggested that there were four main areas of coral reef studies in Lampung Province, namely Lampung bay, Krakatau, Bakauheni, and Lampung west coast. One-way ANOVA analysis of the last 5-year coral data shown there were no spatial differences on coral cover the four areas. Coral cover in Lampung west coast was generally in good shape at 56.13±1.74% and was higher compared to those in Lampung bay, Bakauheni, dan Krakatau regions, at 46.57±2.23%, 36.48±1.58%, and 35.6±3.69%, respectively. All coral data was published through WebGIS at https://sll.itera.ac.id/research/webgis . It is recommended this WebGIS could serve as a reference to conduct long-term coral reef monitoring in Lampung since it provides coordinates and coral reef status as baseline data for further analysis of coral reefs ecosystem.